Etiology and de novo transcriptome analysis of the powdery mildew pathogen on Eucalyptus in Brazil - Fonseca, Natália Risso (2016)
Eucalypt powdery mildew is an important disease that occurs mainly in greenhouses and protected clonal hedges of eucalypt (Eucalyptus spp.) in Brazil. The fungal pathogen infects new leaves and shoots. White superficial colonies isolated or grouped that grow over the affected plant tissue are observed, which can subsequently spread to all leaf surface, causing leaf malformation and reduction on growth and production of shoots for mini-cutting. Because this disease has increased in incidence and importance in recent years, and research on this pathosystem is largely lacking, the objectives of this study were to i) determine the etiology of the disease through ITS and 28S rDNA sequencing and morphological analyses of powdery mildew pathogens isolates collected in different regions in Brazil; and ii) analyze the transcriptome of the powdery mildew pathogen during infection on Eucalyptus urophylla generated by RNA sequencing (RNA-Seq) and de novo assembly. Based on the results of phylogenetic analyses and morphological characteristics, all 42 pathogen isolates collected were identified as Podosphaera pannosa, also known to cause rose powdery mildew. Cross inoculations with pathogen isolates from rose (Rosa spp.) and eucalypt demonstrated that P. pannosa can infect both host species. The transcriptome sequencing by Illumina platform resulted in 12,107 transcripts. Among the 10 most abundant transcripts included genes encoding enzymes involved in fungal establishment and growth. The secretome prediction resulted in 217 proteins, of which 14 were considered as candidate effectors. In addition, 242 primer pairs were designed from the transcriptome sequences with potential to amplify P. pannosa microsatellites (Simple Sequence Repeats – SSR) regions. The results demonstrate that P. pannosa is the only causal agent found for eucalypt powdery mildew. In addition, this study provides technological advances in the study of this disease that will provide a basis for a better understanding of the P. pannosa- eucalypt pathosystem.